1986
DOI: 10.1038/ki.1986.49
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate depletion arrests progression of chronic renal failure independent of protein intake

Abstract: Following 5/6 nephrectomy, 18 rats were fed a normal diet. After 30 days, serum creatinine (SCr), urine protein excretion and urine volume were increased compared to pre-nephrectomy (0.27 +/- 0.1 vs. 1.62 +/- 0.6 mg/deciliter, 17.0 +/- 10.3 vs. 257.6 +/- 13.4 mg/24 hr, and 16.6 +/- 4.4 vs. 39.2 +/- 11.7 ml/24 hr, respectively, all P less than 0.001). At this time, when serum phosphorus (SPi) and serum calcium (SCa2+) were normal, the rats were separated into two groups, matched and paired by body weight and SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…11 The impact of phosphorus level on progression of CKD & on mortality has been examined, with two studies showing different results 4,12 , but the effect of bone-mineral abnormalities on kidney function is unclear. Our study shows that higher serum phosphorus was associated with significantly higher risk for progression of CKD, these findings complements earlier primary studies that showed a beneficial effect of dietary phosphorus restriction on progression of CKD in experimental animals 13 & in humans. 14 Our findings of a significant quantitative interaction between serum phosphorus & calcium levels supports the hypothesis that tissue calcification may be reason behind observed association.…”
Section: Discussionsupporting
confidence: 90%
“…11 The impact of phosphorus level on progression of CKD & on mortality has been examined, with two studies showing different results 4,12 , but the effect of bone-mineral abnormalities on kidney function is unclear. Our study shows that higher serum phosphorus was associated with significantly higher risk for progression of CKD, these findings complements earlier primary studies that showed a beneficial effect of dietary phosphorus restriction on progression of CKD in experimental animals 13 & in humans. 14 Our findings of a significant quantitative interaction between serum phosphorus & calcium levels supports the hypothesis that tissue calcification may be reason behind observed association.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the described effects regarding bone resorption, high PTH may also cause metastatic microcalcifications through elevations in cytosolic Ca (9,10). In rats, Borle et al (16) showed that high P-induced hyperparathyroidism caused nephrocalcinosis. Elevated levels of serum PTH induced intracellular Ca accumulation and Ca-P deposition in renal tissue (16).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high dietary P induced a rapid deterioration of renal function (16). Phosphorus toxicity associates with renal calcium-phosphate precipitation and tubulointerstitial damage, resulting in acceleration of nephrocalcinosis (17).…”
mentioning
confidence: 99%
“…However, aluminum seems to protect lead-induced renal dysfunction in a time-and dose dependent manner. Aluminum has been shown to arrest the chronic renal disease in several experiments (Lemlertgul et al 1986;Shimamura & Okada. 1988).…”
Section: Discussionmentioning
confidence: 99%